RECONCILIATION OF EXPERIMENTAL RESULTS ON H2O SPECIATION IN RHYOLITIC GLASS USING IN-SITU AND QUENCHING TECHNIQUES - Withers A.C.; Zhang Y.; Behrens H. (My University, 1999)
In order to resolve the controversy over how to interpret experimental H2O speciation results using in-situ and quenching techniques, we have carried out an infrared spectroscopic study to determine whether the molecular H2O (5230 cm-1) and OH (4520 cm-1) band intensity variation with measurement temperature below glass transition is owing to species interconversion or to the temperature dependence of molar absorptivities. By comparing rhyolitic glasses with different total H2O content from 0.18 to 0.76 wt.%, we show that the peak height of the 4520 cm-1 band increases by a similar relative amount (about 2% if the baseline is fit with a flexicurve and 10% if the baseline is fit by a straight line) from 25 to 400°C, independent of the total H2O content. The results show that (1) the molar absorptivities do indeed change with temperature, and (2) in our experiments below the glass transition temperature, species concentrations do not change noticeably with temperature, and the band intensity variations are caused mainly by changes in the shape of the absorbance bands with temperature. The absence of unquenchable species reaction in the glass state (on our experimental time scale) confirms that speciation data can be obtained using the quench technique from 400 to 600°C. On the other hand, the temperature dependence of the molar absorptivities must be quantified for the full potential of the in-situ technique to be realised.
Keywords: GLASSES; WATER; CHEMICAL FRACTIONATION; INFRARED SPECTROSCOPY; IN-SITU; MEASUREMENT; ABSORPTION